Alphakids plus: billy banana - Hastings, Jack; Stewart, Chantal (Horwitz Martin Education. Australia, 2001)
"Billy Banana" is a whimsical children's story about a playful monkey named Billy who loves bananas more than anything. The narrative follows his adventures as he embarks on a quest to find the biggest, juiciest banana in the jungle. Along the way, Billy encounters various friends and obstacles, learning valuable lessons about friendship, sharing, and the joy of simple pleasures. The vibrant illustrations and catchy rhymes make it an engaging read for young children, capturing the fun and excitement of Billy's antics while imparting important life lessons.